V. Sackville-West correspondence and poem - Sackville-West, V. (Victoria), 1892-1962.
TLS (1939 May 23) written by Sackville-West to Joseph Auslander enclosing the manuscript (with corrections) of her poem, Winter Afternoon.
English author and poet.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Auslander, Joseph, -- 1897-1965 -- Correspondence; English poetry -- 20th century; Authors, British; Poets, British